1981
DOI: 10.1159/000232771
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Paul-Bunnell (P-B) Antigen-Antibody System

Abstract: The multiple nature of heterophile, Paul-Bunnell (P-B) antigen has been suggested by our previous studies as well as those of others. In the present study, two distinct antigens of P-B specificity were defined by means of hemagglutination and immunodiffusion tests in agarose gel; one antigen (BS) was shared by bovine (BRBC) and sheep red blood cells (SRBC) and another antigen (B) was limited to BRBC. Both anti-BS and anti-B antibodies were shown to be present in sera of 106 patients with infectious mononucleos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…The precipitin in IM sera was shown to be the P-B antibody and the precip itinogen in syphilis and leprosy sera was shown to be long to the P-B antigenic complex and to be closely related to the previously described B antigen of this complex [5], As mentioned above, in our previous investiga tions [1][2][3][4], we noted P-B antigen in human pathologi cal tissues and sera. In one study [3] we demonstrated the B antigen in 28% of lymphoma-leukemia sera test ed.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…The precipitin in IM sera was shown to be the P-B antibody and the precip itinogen in syphilis and leprosy sera was shown to be long to the P-B antigenic complex and to be closely related to the previously described B antigen of this complex [5], As mentioned above, in our previous investiga tions [1][2][3][4], we noted P-B antigen in human pathologi cal tissues and sera. In one study [3] we demonstrated the B antigen in 28% of lymphoma-leukemia sera test ed.…”
Section: Discussionsupporting
confidence: 51%
“…This appar ent discrepancy can be explained by the difference in sensitivity of the tests used. The HI test used in the previous study on lymphoma-leukemia detects the P-B antigen in a concentration as low as a few nano grams per milliliter, whereas the precipitation test used for the study on syphilis and leprosy requires this antigen at a concentration of a few micrograms per milliliter [3][4][5]. On the other hand, we noted previ ously P-B antigen at precipitating concentration in a few sera of patients with malignancies and rheuma toid arthritis [4], Several years ago, it was proposed that P-B anti bodies detected in the course of IM are formed in re sponse to the stimulus exerted by P-B antigen(s) ap pearing in the course of the disease as a result of the pathological process [ 14, see also 15,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Agglutination tests with trypsinized bovine red blood cells (BRBC) and sheep red blood cells (SRBC) were performed with sera of CHS patients and their mothers following the routine procedures established in our laboratory [7][8][9], Mixed agglutination (MA) tests with tissue sediments of guinea pig kidney (GPK) and trypsinized BRBC as the indicator cells were performed following the principle of the proce dure that was used for detection of Paul-Bunnell (P-B) antigen on spleen cells of lymphoma-leukemia patients [10]; the procedure will be described in detail elsewhere [11]. Enzyme immunoassay (EIA) with high molecular weight glycoprotein (HMWGP) of BRBC 1 Supported by Research Grant CA-27628 from the National Cancer Institute (a), the Richard W. and Mae Stone Goode Estate (a), and by a research grant from Funda Vargas, Fundaciencia and Funda Polar (b).…”
mentioning
confidence: 99%